Experimental study on the performance of an active novel vertical partition thermal storage wallboard based on composite phase change material with porous silica and microencapsulation. (15th January 2022) - Kong, Xiangfei; Jiang, Lina; Yuan, Ye; Qiao, Xu
Abstract: In this study, a microencapsulated phase change material (MPCM) was mixed with a composite phase change material (CPCM) made of porous silica/paraffin to produce hybrid PCMs (C-MPCM), and then prepared two types of gypsum-based PCM wallboards (model A, which is M-A for short henceforth: Split; and model B, which is M − B for short henceforth: Hybrid). After that the physical properties and microstructure of the samples were evaluated. The results showed that paraffin wax was well immersed in porous silica with an optimal adsorption rate of 70% with no leakage. Meanwhile, the CPCM maintained good chemical compatibility and thermal stability. In addition, the thermal properties of PCM wallboards and gypsum wallboard were studied through an automatically controlled test system. Thermal performance showed that, both the M-A/B wallboards were able to keep the temperatures of room A/B within the thermal comfort range throughout the year. M-A wallboard was more energy efficient than M − B wallboard in summer working conditions; M − B wallboard was more energy efficient in winter working conditions. The total water supply duration consumed by M − B wallboard was far less than that of M-A wallboard. Considering comprehensively, M − B wallboard is more suitable for practical application in building energy saving. Highlights: A new type of hybrid PCM (C-MPCM) was prepared. An active non-load-bearing partition PCM wallboard was invented. A system was developed to test the thermal performance of wallboards.